Bakteri Resisten Timbal (Pb) dari Sedimen Sungai Tercemar Industri Sebagai Agen Bioremediasi : Literature Review - Leli Agustina Pane; Rabithah Hanny Sembiring (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Heavy metal pollution, particularly lead (Pb), is one of the most serious environmental problems resulting from industrial activities, mining, and domestic waste. Lead is toxic, persistent, and readily accumulates in river sediments, posing significant risks to ecosystem stability and human health. One of the most effective, economical, and environmentally friendly methods for addressing this pollution is bioremediation using indigenous bacteria that have naturally adapted to contaminated environments. This study aims to evaluate the potential of lead-resistant bacteria isolated from contaminated river sediments as bioremediation agents through a literature review approach. A systematic literature search was conducted using the Google Scholar, PubMed, NCBI, and Elsevier databases, focusing on articles published between 2020 and 2026. A total of ten articles meeting the inclusion criteria were analyzed descriptively. The review findings indicate that bacteria belonging to the genera Bacillus, Pseudomonas, Micrococcus, Klebsiella, Acinetobacter, Serratia, Raoultella, Aeromonas, and Moraxella possess resistance to heavy metals through mechanisms such as biosorption, bioaccumulation, biofilm formation, exopolysaccharide production, and cellular detoxification systems. Several studies reported remarkably high Pb removal efficiencies, ranging from 80% to 99.99%, with bacterial growth maintained in media containing lead concentrations of up to 100 ppm. Among these, the genera Bacillus and Pseudomonas were the most frequently identified and demonstrated the greatest potential as bioremediation agents.